A Study of Effect of Ten Week Circuit Training Program on Physical Fitness Level of Athletes: Assessing the Impact of a Ten Week Circuit Training Program on the Physical Fitness of Athletes (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Coaching at thepresent is necessarily based on complete and systematic information derivedfrom scientific work. One the most important fact in coaching is to know thepresent state of the athletes with regard to his technical efficiency andphysiological capacities, which are harmonized later in the form of tactics.